FIRST REPORTED CASE OF DOG ASSOCIATED PIG RABIES IN GHANA - Tasiame, William; Folitse, O. Raphael; Emikpe, O. Benjamin; Adongo, Awuni Joseph (African Journal of Infectious Diseases (AJID), 2015)
Background: Pig rabies is uncommon and there is paucity of information on rabies in pigs in West African countries other than Nigeria. Thiscommunication presents a case of dog associated pig rabies in Adidome, Ghana.Materials and Methods: Case history, Dog assessment in adjoining communities, human exposure, clinical presentations and mortality in affectedpigs were evaluated using standard techniques. Laboratory screening of brain samples collected was by Fluorescent antibody technique.Results: Stray dog bitten affected pigs showed anorexia, constipation, hyper excitation, twitching of head, roaring and foaming with resultantcategory 1 and 11 human exposure, 17% mortality and 75% case fatality rate. Laboratory examination of swine brain specimens tested positive forRabies virus using Fluorescent Agglutination Test.Conclusion: This report described the first documented case of dog associated pig rabies in Ghana and emphasis was laid on continued advocacy andprompt reporting of suspected neurological conditions in pigs in Ghana